Evaluasi Kinerja Simpang Jl. Dr. Wahidin Sudiro Husodo – Jl. Mayjen Sungkono Terkait Pembangunan Underpass GKB Gresik - Cahyono, Muhammad Shofwan Donny; Muhtadhi, Adhi; Wibisono, R. Endro (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2021)
The high growth rate of vehicles gives direct effect on high road traffic. The capacity of Surabaya-Gresik Highway, which is designed with 2 lanes on each lane, is no longer able to accommodate the existing traffic load. This is proven by frequent long traffic jams on Jalan dr. Wahidin S.H. Therefore it is the right time to construct the underpass.The purpose of this research was to define the peak hours, the degree of saturation, and the level of service that occurred on the road section of Dr. Wahidin S.H to the intersection of Gresik Grand Mosque due to the construction of the underpass in GKB Gresik. The method used in this study was identification of traffic character, traffic survey, and analysis of traffic performance of signalized intersections using the Indonesia Highway Capacity Manual. The results of the study were morning and afternoon peak hours. In the existing condition in 2020 the value of Saturation Degree (DS) was 0.858 > 0.75 (LOS) E. In 2026 in which it is 5-year prediction by using management of traffic engineering the value of degree saturation (DS) was 0.744 < 0.75, level of service (LOS) C. Conditions after management of traffic engineering with adjustment of traffic light time cycle at the intersection of Jl. Dr. Wahidin S.H. – Jl. Gresik – Babat – Jl. Mayjen Sungkono, widening of intersection geometry and the operation of left and right side frontage and setting of Traffic Signaling Equipment (APILL) showed a level of service (LOS) C, stable flow, but limited speed.